DETERMINATION OF NUTRIENT COMPOSITIONS, GLYCEAMIC INDEX AND ANT-DIABETIC POTENTIALS OF MULTI-PLANT BASED FUNCTIONAL FOODS IN RATS - Steve, Ijarotimi Oluwole (Journal of Food and Pharmaceutical Sciences, 2015)
Background: Nutrition transition, that is, increase in consumption of high energy-dense foods, with low consumption of fruits and vegetables, has been implicated as the major factors responsible for the increase in prevalence of diet-related diseases such as diabetes and cardiovascular diseases worldwide. Evidence has shown that consumption of plant-based foods prevents the risk of these chronic diseases, hence, the present study formulated and evaluated nutrient compositions and antidiabetic potentials of multi-plant based functional foods from locally available food materials.Methods: Food materials (popcorn, moringa leaves, wonderful kola and defatted soybean) were obtained from reputable farms and markets in Akure, Nigeria. The food materials were processed as raw, blanched and fermented flour samples, and blended to obtain nine samples, i.e., R1, B1 and F1 (popcorn 60%, soybean 10%, moringa 20% and groundnut oil 10%), R2, B2 and F2 (popcorn 60%, soybean 10%, wonderful kola 20% and groundnut oil 10%) and R3, B3 and F3 (popcorn 60%, soybean 10%, moringa 10%, wonderful kola 10% and groundnut oil 10%) usingÂ  Nutri-Survey software. Proximate compositions of the blended samples were determined using AOAC methods, and glyceamic index and anti-diabetic potentials were determined using rat models.Results: Proximate compositions (g/100g) of the formulated multi-plant based functional foods were as follows: moisture contents ranged from 6.29 in F3 to 8.27 in R3, crude fiber contents from 2.79 in F2 to 4.68 in B3 and crude protein contents from 23.22 in B1 to 30.39 in F3, while carbohydrate content of the formulations ranged from 52.10 in F3 sample to 56.94 in B2 sample, while energy values were between 421.1 in R1 and 433.7 kcal in B1. Glycaemic index (GI) of the formulated functional foods ranged from 5.8% in R3 to 28.9% in R1 sample, and were significantly (<0.05) lower than in glucose (a reference sample). The glycaemic load (GL) of R4 sample had the lowest value (3.3), while F4 sample had the highest value (15.1). The percentage blood glucose reduction of diabetic-induced rats fed with R1samples (63.8%) had the highest values; while those rats fed with B2 sample (24.1%) had the lowest blood glucose reduction. Statistically, the percentage blood glucose reduction of the formulated functional foods, particularly R1 and F1, were comparable to metformin (a synthetic anti-diabetic drug) in terms of antidiabetic activities. Â Conclusion: The study reported on the nutritional profile of multi-plant based functional foods from popcorn, soybean, wonderful kola and moringa leaves. Findings showed that these functional foods contain appreciable amount of protein, fiber, carbohydrate content within the recommended value for diabetic patients, low glycaemic index and glycaemic load properties and with antidiabetic activities. Hence, the formulated functional foods may be suitable for individuals at risk of diabetes or diabetic patients.